Children with Kawasaki disease or Kawasaki-like syndrome (MIS-C/PIMS) at the time of COVID-19: are they all the same? Case series and literature review - A. Marino (Reumatismo, 2021)
Since the coronavirus disease 2019 (COVID-19) outbreak started, children have been considered marginally involved compared to adults, with a quite significant percentage of asymptomatic carriers. Very recently, an overwhelming inflammatory activation, which shares clinical similarities with Kawasaki disease (KD), has been described in children exposed to COVID-19. We report three KD-like cases that occurred during the pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in a highly affected area of Northern Italy. The clinical presentation was characterized by the presence of unremitting fever, diarrhea and elevated inflammatory markers. Case #1 and Case #2 occurred one week apart and shared other clinical features: laboratory tests confirmed COVID-19 exposure and high inflammatory activation with myocardial involvement. Case #3 followed a more typical pattern for KD. Interestingly, this patient showed lower levels of procalcitonin, C-reactive protein, D-dimers, and ferritin compared to the other two cases, whereas platelet count was higher. We hypothesize that SARS-CoV-2 might act in children as a trigger, either inducing a classical KD phenotype or causing a systemic inflammatory response leading to a severe KD-like phenotype, eventually characterized by myocardial impairment. We think that bringing these cases and their differences to the attention of the rheumatology community during the COVID-19 pandemic will be beneficial in order to highlight the importance of early diagnosis and to increase awareness of this new phenomenon.